The effect of porosity on the corrosion rate of aluminum foam as a sacrificial anode - Prayitno, Dody; Riyono, Joko (Journal of Integrated and Advanced Engineering (JIAE), 2024)
The objective of this paper is to investigate the effect of porosity on the corrosion rate of aluminum foams as sacrificial anodes. An aluminum bar (6061 series) was cut to 19x19x13 mm. Then the aluminum was drilled to become an aluminum foam. A Carbon steel plate was cut to 40x 40x1 mm. The aluminum foam and the steel were connected by a bolt to become a galvanic couple. The galvanic couples were immersed in fresh water for variation times (32 hours, 168 hours, 335 hours, 504 hours and 672 hours). The temperature was 27 oC. The corrosion test was the weight loss method. The results. The corrosion rate of initial steel is 0.15 millimeter per year (mmy). The corrosion rate of steel decrease from 0.15 mmy to 0.015 + 0.02 mmy when using the aluminum foam as sacrificial anode. The corrosion rate of initial aluminum foam is 0.01 mmy. The corrosion rate of aluminum foam increases from 0.01 to 0.015 – 0.02 mm when used as sacrificial anode. Increasing the porosity of the anode will reduce the corrosion rate of the anode itself.